2017
DOI: 10.1111/1759-7714.12423
|View full text |Cite
|
Sign up to set email alerts
|

Salvage surgery for primary lung cancer after chemotherapy in octogenarians

Abstract: An 81‐year‐old female patient was admitted to our institute because of abnormal X‐ray results. Chest computed tomography showed a 7.7 × 5.3 cm mass located in the left lower lobe and multiple swollen lymph nodes. 18F‐fluorodeoxyglucose‐positron emission tomography indicated high standard uptake values in the mass and swollen lymph nodes. The patient was diagnosed with stage cT3N2M0‐IIIA squamous cell carcinoma. Although the patient had multiple lymph node metastases and severe obstructive pulmonary function, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Salvage surgery already plays a role in the treatment of esophageal cancer, colorectal cancer and other tumors . In recent years, salvage surgery has also been introduced into the treatment strategy of advanced lung cancer after chemotherapy/radiotherapy failure . In a study conducted by Hidetaka et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvage surgery already plays a role in the treatment of esophageal cancer, colorectal cancer and other tumors . In recent years, salvage surgery has also been introduced into the treatment strategy of advanced lung cancer after chemotherapy/radiotherapy failure . In a study conducted by Hidetaka et al .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In recent years, salvage surgery has also been introduced into the treatment strategy of advanced lung cancer after chemotherapy/radiotherapy failure. [18][19][20][21][22] In a study conducted by Hidetaka et al a complete pathological response was found in nearly half the cases who received salvage surgery after chemotherapy/radiotherapy. 23 However, the role of salvage surgery in patients with advanced lung cancer after targeted therapy has still not been well reported in the literature.…”
Section: Introductionmentioning
confidence: 99%